Intensity Dependence of Conductivity in Aqueous NaCl Solution at Microwave Frequency - Jia, Guo-Zhu; Huang, Ka-Ma; Yang, Xiao-Qing; Yang, Li-Jun (Asian Journal of Chemistry, 2011)
The influence of high power electromagnetic fields on conductivity of aqueous NaCl solution at microwave frequency was studied. It was found that microwave field-induced change of conductivity on the system is more significant at higher power. When the intensity of microwaves was above 104 V m-1, our calculation indicated conductivity in the solution were interrelated on intensity of microwave we took advantage of rotational langevin equation to simulate dynamics of average hydrogen bond in aqueous NaCl solution in external microwave fields. The results agreed well with experiments. The strongly nonlinear change could be categorized as one of microwave nonthermal effects.